2019
DOI: 10.20853/33-6-2939
|View full text |Cite
|
Sign up to set email alerts
|

Improving student assessment feedback in an introductory accounting course through two-stage collaborative assessment

Abstract: Student feedback is an important part of the formative assessment process. Previous research shows that there is room for improvement in student feedback on accounting education. Various benefits, especially those associated with the development of certain pervasive skills through group learning, have been established through research. The two-stage group examination offers students the opportunity to become active participants in the feedback process, while harvesting the benefits of teamwork. This study invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Assessment is defined as a continuous process that occurs before, during and after schooling and can be classified as summative or formative (Kruger, 2019). The summative assessment focuses on judgement, measurement and report of learners' progress, whilst AfL, also known as formative assessment, concerns itself with the diagnostic information used by the teacher to determine the next step to advance learning (Black & Wiliam, 2018;Darong & Niman, 2021).…”
Section: Assessment In Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment is defined as a continuous process that occurs before, during and after schooling and can be classified as summative or formative (Kruger, 2019). The summative assessment focuses on judgement, measurement and report of learners' progress, whilst AfL, also known as formative assessment, concerns itself with the diagnostic information used by the teacher to determine the next step to advance learning (Black & Wiliam, 2018;Darong & Niman, 2021).…”
Section: Assessment In Accountingmentioning
confidence: 99%
“…From these responses, it is evident that the AfL practices implemented in the classrooms are practical and seek to develop the learners' knowledge and skills in Accounting. The different responses recognise assessment in Accounting as a continuous process, and the diverse types of tasks provide the learners with an opportunity to practice and improve competency in the subject (Kruger, 2019).…”
Section: Assessment In Accountingmentioning
confidence: 99%
“…There are a few studies in Accounting Education that have investigated the integration of educational technology in assessment to improve learner academic performance. 15 Anyanwu, Govender and Ngwenya studied the integration of technology in Business Education in Nigeria, and their findings exposed a poor investment in technology integration in schools which affected the pedagogical implementation. 16 Similarly, Skhepe and Matashu conducted a study on using technology in an Accounting classroom in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another research by (Pitt & Norton, 2017) on using a focus group/cooperative learning to give feedback found that the lifelong learning of future accountants is enhanced. This idea is supported by Kruger (2020), who researched giving feedback to introductory accounting courses and improving student assessments by providing feedback through two-stage collaborative assessment, concluding that feedback offers students the opportunity to become active participants in the process while harvesting the benefits of teamwork while also establishing their mistakes for improvement and future performance. Other ways include a classroom set-up, after formative assessments, and during classroom presentations using ICT (Wong & Yang, 2017).…”
Section: Using the Focus Group Or Classroom Way To Give Feedbackmentioning
confidence: 99%